Pengujian Website E-Learning Universitas Pamulang Menggunakan Metode Black Box Testing Equivalence Partitioning - Bangun Suprianto; Irfan Alamsah; Jepri Afrizal; Khoiriyah; Wike Rahayu; Ahmad Fauzi (CV. Multi Kreasi Media, 2023)
The e-learning application is a website-based application that is used by students to view academic information. To ensure that the website is in accordance with their needs, it is necessary to test the e-learning website by utilizing the equivalence partitioning technique to see the suitability of functions according to the expectations and needs of the user. Black Box Testing is one of the software programs software that checks strategies that specialize in functionality, especially the use and operation of applications (easy according to what is expected or not) use of the Equivalence Partitioning Method Equivalence partitioning is an automatic check or blackbox check that divides the input area into information classes and and with help classes the information is fetching see examples can be derived As a result of this and checking it was found there are some bugs errors like character and data type restriction in username input.